2014
DOI: 10.1016/j.ajem.2014.07.034
|View full text |Cite
|
Sign up to set email alerts
|

Can the new McGrath laryngoscope rival the GlideScope Ranger portable video laryngoscope? A randomized manikin study

Abstract: The intubation performance of novices using the McGrath MAC was equal to their performance using the GlideScope Ranger in regular simulated airways.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 20 publications
2
26
0
1
Order By: Relevance
“…Therefore, the POGO was scored both in the head-flat and head-elevated positions in all patients, but the trachea was intubated only once. Because the McGrath MAC videolaryngoscope has a regular Macintosh-type blade, 5 we decided to use a slightly modified plain tracheal tube instead of a styletted tube. The tracheal tube was bent to exaggerate its curvature, allowing it to pass anteriorly into the larynx 19 (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the POGO was scored both in the head-flat and head-elevated positions in all patients, but the trachea was intubated only once. Because the McGrath MAC videolaryngoscope has a regular Macintosh-type blade, 5 we decided to use a slightly modified plain tracheal tube instead of a styletted tube. The tracheal tube was bent to exaggerate its curvature, allowing it to pass anteriorly into the larynx 19 (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4] The McGrath MAC videolaryngoscope (Aircraft Medical Ltd., Edinburgh, UK) is a recently developed videolaryngoscope incorporating a regular Macintosh-type blade. 5 However, there has been some debate regarding the time to tracheal intubation (TTI) and success rates in patients with normal and known difficult airways. [5][6][7][8][9][10] Recently, a meta-analysis of paediatric videolaryngoscopes demonstrated that their use did not result in increased intubation success rate or reduced intubation time, even though visualisation of the glottis was improved compared with direct laryngoscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iwai et al [18] and Griesdale et al [19] also reported high success rates using GlideScope in patients with restricted airway access. Kim et al [20] reported that the intubation performance of novices using the McGrath MAC was equal to their performance using the GlideScope Ranger in regular simulated airways.…”
Section: Discussionmentioning
confidence: 98%
“…L'exposition glottique est meilleure qu'avec un laryngoscope classique [23]. Il permet le plus souvent l'intubation en cas d'échec avec le laryngoscope classique, y compris dans des conditions difficiles.…”
Section: Laryngoscopie Indirecteunclassified